Estructuración del programa de seguridad, salud en el trabajo y ambiente para la empresa NEM basado en la guía para contratistas RUC (2022)
Safety and health at work is important for any organization, especially for its profitability, given that when each worker knows the risks to which they are exposed during their working day, they participate and become aware of the prevention of diseases or injuries.